2012
DOI: 10.3348/kjr.2012.13.3.350
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Pulmonary Capillary Hemangioma: Dynamic Contrast-Enhanced CT and Histopathologic Findings

Abstract: We report the dynamic contrast-enhanced CT and histopathologic findings of a rare case of recurrent pulmonary capillary hemangiomas. The findings consisted of peripheral nodular enhancement at the early arterial phase and a subsequent "central filling-in" enhancement pattern on the delayed scans, which was identical to the well-known enhancement pattern of hemangiomas of the liver. Although there was no evidence of histological malignancy, pulmonary capillary hemangiomas manifested as multiple nodular lesions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 10 publications
(17 reference statements)
2
13
0
Order By: Relevance
“…Both discovered radiologically as nodules frosted glass [9]. Eun Young Kim and al also reported two cases of pulmonary hemangiomas shaped solitary nodules [1]. In both cases, the diagnosis of bronchogenic carcinoma was argued before the pathology results confirmed the diagnosis of hemangioma.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Both discovered radiologically as nodules frosted glass [9]. Eun Young Kim and al also reported two cases of pulmonary hemangiomas shaped solitary nodules [1]. In both cases, the diagnosis of bronchogenic carcinoma was argued before the pathology results confirmed the diagnosis of hemangioma.…”
Section: Discussionmentioning
confidence: 82%
“…Two cases of recurrence has been reported in the literature [1,10] one of them is a young woman of 22 years, 50 months after resection of pulmonary left nodules, which the anatomopathology study confirmed angiomatosis origin. New pulmonary nodules were detected in a chest radiograph.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority was found in trachea4 but isolated endobronchial lesion2,8 has been relatively infrequent. In Korean literature, several cases of tracheal capillary hemangioma3,4 and pulmonary capillary hemangioma5 were reported, and a case of capillary hemangioma of left main bronchus in an infant was reported9.…”
Section: Discussionmentioning
confidence: 99%
“…Capillary hemangiomas of tracheobronchial trees are very rare in both adults and infants2. In Korean literature, there have been several reports of capillary hemangioma of adult trachea3,4 and lung parenchyma5, but none has been reported to date in the lobar bronchus of adults. We report a case of isolated endobronchial capillary hemangioma in adult, which was diagnosed with pathologic examination of the forcep biopsied specimen.…”
Section: Introductionmentioning
confidence: 99%